2006
DOI: 10.1007/s10681-006-9312-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of plant height by molecular markers using a population of recombinant inbred lines in maize

Abstract: Plant height is an important trait for maize breeding because it is related to planting density and lodging resistance. It is influenced by many qualitative genes and quantitative trait loci (QTL). In this study, the genetic basis of plant height and its related traits were dissected, using simple sequence repeat (SSR) markers with a maize population of 294 recombinant inbred lines (RIL). Correlation results showed that plant height had a significant positive correlation with leaf number, average internode len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…For example, during the green revolution, the introduction of semi-dwarf varieties into wheat ( T. aestivum L.) appropriately reduced PHT and contributed significantly to a worldwide increase in potential grain yield (Peng et al 1999). PHT is known to be typically under polygenic control (Bellucci et al 2015; Tang et al 2007). Thus, identification of QTL/gene controlling PHT would help to improve the efficiency of designed breeding in wheat.…”
Section: Introductionmentioning
confidence: 99%
“…For example, during the green revolution, the introduction of semi-dwarf varieties into wheat ( T. aestivum L.) appropriately reduced PHT and contributed significantly to a worldwide increase in potential grain yield (Peng et al 1999). PHT is known to be typically under polygenic control (Bellucci et al 2015; Tang et al 2007). Thus, identification of QTL/gene controlling PHT would help to improve the efficiency of designed breeding in wheat.…”
Section: Introductionmentioning
confidence: 99%
“…Plant height and ear height are decisive factors to plant density and lodging resistance [20, 40]. In this study, we studied the genetic basis underlying PH and EH with a RIL based design III.…”
Section: Discussionmentioning
confidence: 99%
“…The mQTL on chromosome 10 was also confirmed by Messmer et al (2011) for chlorophyll level and leaf senescence under drought and optimal conditions. Besides SG traits, the mQTL regions on chromosomes 1 and 10 have also been found to be constitutively regulating plant height under both the water regimes across temperate and tropical germplasm (Tang et al 2007; Salvi et al 2011; Chen et al 2011; Cai et al 2012a, b). Notably, most of the studies reported the QTL for SG traits on chromosome 10 (10.04–07) to be of large effect ( R 2  > 10 %), which indicates potential for marker-assisted introgression in future in pedigree and back-cross-based line improvement programmes.…”
Section: Discussionmentioning
confidence: 99%